BIOLOGICAL ASPECTS OF PAPILIO PERANTHUS (LEPIDOPTERA: PAPILIONIDAE) AS OBSERVED AT BUTTERFLY RESEARCH FACILITY - LIPI, CIBINONG, INDONESIA - Djunijanti Peggie (BRIN Publishing (Penerbit BRIN), 2019)
Papilio peranthus is endemic to Indonesia, where it occurs on several islands and island groups. This beautiful butterfly is extensively traded, thus efforts to breed this species are very desirable. Captive breeding research was conducted on P. peranthus during September 2016 to December 2018. In total, 221 individuals were available for observation. Data on the life cycle of the species, together with observations on females being approached for mating, and female oviposition after mating, are presented. The result demonstrate that P. peranthus is not monogamous. Observations on other biological aspects are also reported.